Laparoscopy in the Management of Lumboperitoneal Shunt Catheter in Obese Patients with Pseudotumor Cerebri - Ozturk, S.; Cakin, H.; Karabulut, K.; Pasahan, R.; Kaplan, M. (Medknow Publications & Media Pvt Ltd, 2018)
Lumboperitoneal shunts are widely used for the treatment of patients diagnosed with pseudotumor cerebri (PTC). Obesity is a risk factor for PTC. In particular, catheter migration out of the abdominal cavity is more commonly observed in morbidly obese patients. The aim of this study was to discuss the underlying mechanisms of catheter migration and treatment modalities in morbidly obese patients with PTC. The present study included four morbidly obese patients. All cases had undergone the previous laparotomy for insertion of a distal catheter into the abdominal cavity. In three cases, migration of the distal catheter out of the abdominal cavity was observed. Migration of the proximal tip of the catheter out of the spinal canal was observed in the fourth case. In all cases, laparoscopic revision surgeries were performed. During revision surgery, a catheter tunnel was prepared immediately over the external oblique fascia to obtain the shortest and deepest tunnel, and a distal catheter was inserted by laparoscopic guidance posterolaterally, i.e., through the postaxillary line. None of the patients developed any complications during the follow-up period of 4 years. We recommend laparoscopic insertion of distal catheters through the postaxillary line into the abdominal cavity using as short a catheter route as possible. Thus, tension and traction on the catheter due to abdominal movements can be decreased in morbidly obese patients to prevent catheter migration.
Keywords: Laparoscopy; lumboperitoneal; migration; obesity; pseudotumor cerebri; shunt